The Effects of Environmental, Social, and Governance (ESG) on Market Structure: A Study of Commercial Banks in Indonesia - Hilda, Wimvi; Yenny Kornitasari (Contemporary Studies in Economic, Finance and Banking, 2025)
Banks play an important role in the economy and demonstrate their commitment to sustainable economic development through Corporate Social Responsibility (CSR) by highlighting social, economic and environmental aspects. The purpose of this study is to analyze the influence of environmental, social, and governance aspects as dependent variables on market structure as measured by the Lerner Index as an independent variable. Four commercial banks in Indonesia were selected as samples and panel data regression methods were used in the analysis. The results show that environmental aspects have a positive and significant influence on the market structure of monopolistic competition. In contrast, the social aspect does not show significant influence, and the governance aspect is influential but with a negative direction towards the monopolistic market structure. Therefore, these results suggest that banks consider these aspects in their operations and policies to create a healthier and more competitive market.